1966
DOI: 10.1136/bmj.2.5528.1481
|View full text |Cite
|
Sign up to set email alerts
|

Medical vagotomy: an assessment.

Abstract: Attempts have been made to predict the secretion of gastric acid after surgical vagotomy with a drainage procedure, by blocking the vagus nerves with atropine and hexamethonium or with propantheline in preoperative tests (McArthur, Tankel, and Kay, 1960;Gillespie and Kay, 1961;Checketts, Gillespie, and Kay 1966). These workers carried out two tests on their subjects before operation: the first was an augmented histamine test (Kay, 1953); in the second hexamethonium bromide 50 mg. and atropine 0.325 mg., or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1967
1967
1975
1975

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…J., 1968), and controlled clinical trials of selective vagotomy are indicated to assess these points. Johnston, Goligher, and Duthie (1966) have claimed that complete vagotomy will prevent jejunal ulceration regardless of the initial acid secretion, and our experience supports this. However, in patients with an initial high acid secretion, an incidence of incomplete vagotomy of 35% would expose too many of these patients to a high risk of jejunal ulceration.…”
Section: Metabolic Studiessupporting
confidence: 71%
See 1 more Smart Citation
“…J., 1968), and controlled clinical trials of selective vagotomy are indicated to assess these points. Johnston, Goligher, and Duthie (1966) have claimed that complete vagotomy will prevent jejunal ulceration regardless of the initial acid secretion, and our experience supports this. However, in patients with an initial high acid secretion, an incidence of incomplete vagotomy of 35% would expose too many of these patients to a high risk of jejunal ulceration.…”
Section: Metabolic Studiessupporting
confidence: 71%
“…The lowest residual (post-vagotomy) secretion in the latter group was 17 HCl (m-equiv/hr), and the lowest pre-vagotomy secretion was 22 HCl (m-equiv/ hr) in the post-histamine hour. The reason for this finding is obscure, but preferential interference with the inhibitory or protective mechanism in the duodenum is a possible explanation (Johnston, Goligher, and Duthie, 1966).…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…The insulin test is used to evaluate the completeness of surgical vagotomy but interpretation of the results has been the subject of recent controversy (Johnston, Goligher, and Duthie, 1966). There is general agreement that a complete vagotomy has been carried out if the acid concentration rises less than 20 m-equiv/1.…”
Section: Minnesota Multiphasic Personality Inventory (Mmpi)mentioning
confidence: 99%
“…Recently screening of the tube was omitted in some studies (Johnston, Goligher & Duthie, 1966) w-hich, of course, is a retrograde step. Aspiration Continuous aspiration is recommended in order to avoid the effect of gastric emptying on total collection.…”
Section: Screening Of the Tubementioning
confidence: 99%